PENGARUH MOTIVASI BELAJAR DAN STATUS SOSIAL EKONOMI ORANG TUA TERHADAP MINAT MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI - Sri Siti Nuraini; Ai Nur Solihat; Kurniawan Kurniawan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research was motivated by the low interest of students in continuing their education to tertiary institutions, this can be seen from the student graduation data over a 5 year period obtained from the school. This research aims to determine the influence of learning motivation and parents' socio-economic status on interest in continuing their education to higher education. This research is quantitative research using a survey method with an ex post facto design. The population of this study were all 89 class XII students. The sampling technique was saturated samples. Data was obtained from distributing questionnaires. The research results show that learning motivation influences interest in continuing education to college. Parents' socio-economic status influences interest in continuing education in college. Then, learning motivation and parents' socio-economic status together influence interest in continuing their education to college. The conclusion of this research is that learning motivation and parents' socio-economic status influence interest in continuing their education to college.